(untitled) (Revista de Educação Pública, 2013)
Este artigo apresenta um recorte de pesquisa sobre a formação do pedagogo e o ensino da Matemática. Indaga-se: o professor graduado em Pedagogia, para ensinar a Matemática nos anos iniciais do Ensino Fundamental, enfrenta que desafios? Para realizar este estudo, utiliza-se o questionário, a entrevista semiestruturada e a análise de documentos. Analisa-se a organização dos currículos de cinco cursos de Licenciatura em Pedagogia no Estado de Mato Grosso. O resultado da investigação evidencia que os desafios enfrentados residem na formação do professor e na organização da escola. Abstract This article presents a research outline about the formation of the pedagogue and the teaching of Mathematics. It is questioned: the graduated teacher in pedagogy, to teach mathematics in the Initials Years of fundamental teaching, face what challenges? In order to realize this study, it was used the questionnaire, the semistructured interview and the analysis of documents. It is analyzed the organization of curriculae of five courses of licensing in Pedagogy in the state of MatoGrosso. The result of the investigation evidences that the challenges faced reside in the teacher formation and in the school organization. Keywords: Teachers’ formation. Pedagogy. Mathematics Teaching.